James McGill of Montreal - Frost, Stanley Brice (McGill-Queen's University Press, 1995)
Keywords: McGill, James; Université McGill

Transforming the Ideal: Visions and Revisions of Housing in a French-Canadian Community, 1942-1995 - Gilliland, Jason A. (Université McGill, 1996)
Keywords: Cité-Jardin du tricentenaire; Logement

Modular Prefabrication versus Conventional Construction as a Cost Effective Alternative for the Construction of Single Family Detached Housing in the Montreal Area - Wiedemann, Stefan J. (Université McGill, 1990)
Keywords: Logement

La relation entre l'évolution du salaire réel et de l'emploi: Montréal, 1963-1982 - Dagenais, Vincent (Université McGill, 1990)

Destination, Housing and Quality of Life in the Migrant Experience from Larino (Molise, Italy) to Milano and Montreal - Fainella, John G. (Université McGill, 1996)
Keywords: Italiens; Logement

Working for Family, Nation and God: Paternalism and the Dupuis Frères Department Store, Montreal, 1926-1952 - Matthews, Mary Catherine (Université McGill, 1997)
Keywords: Commerce de détail; Dupuis Frères; Magasins; Travail

La motorisation ou "La rançon du progrès". Tramways, véhicules-moteurs et circulation (Montréal, 1900-1930) - Veilleux, Denis (Université McGill, 1998)
Keywords: Automobile; Tramways; Transport en commun

Les aubergistes et les cabaretiers à Montréal en 1700 - Poliquin, Marie-Claude (Université McGill, 1996)
Keywords: Auberges

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Salubrious Settings and Fortunate Families: The Making of the Golden Square Mile, 1840-1895 - MacLeod, Roderick (Université McGill, 1998)
Keywords: Anglophones; Golden Square Mile; Protestants; Quartiers

Loft Conversions in a Local Context: The Case of Inner City Montreal - Podmore, Julie (Université McGill, 1994)
Keywords: Logement

Community Response to Environmental Change: A Case Study of Montreal's West Island 1981-1991 - Adams, Jennifer (Université McGill, 1992)
Keywords: Quartiers; West Island

Mutual Aid Networks in Two Feminist Housing Co-Operatives in Montreal - Yasmeen, Gisèle (Université McGill, 1991)
Keywords: Féminisme; Logement

Uncompleted Condominiums: A Strategy for Cost Reduction in Montreal Housing - Kowalska, Danuta (Université McGill, 1991)
Keywords: Logement

The Restructuring of the Montreal Tourism Industry: A Sectoral Analysis - Pohlmann, Corinne (Université McGill, 1994)
Keywords: Tourisme

Industry and Space: the Making of Montreal's Industrial Geography, 1850-1918 - Lewis, Robert D. (Université McGill, 1992)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne